2015
DOI: 10.1088/0964-1726/24/10/105001
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of a metal core PVDF fiber for an air flow sensor

Abstract: To track prey or avoid predators, many arthropods can detect variations in airflow and pressure gradients using an array of very thin and sensitive filiform hairs. In this study, metal core piezoelectric poly(vinylidene fluoride) (PVDF) fibers were prepared to mimic such hair sensors. The flexibility of the fibers was very good, which was helpful for overcoming the typical brittleness of piezoelectric ceramic fibers. At the same time, the diameter of the fibers was very small (down to 50 μm in diameter). In or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Similar to the efforts of [13], a post-deposition electrical poling was required to align the dipoles. Single layer samples could be post poled, though the area of poling was quite small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the efforts of [13], a post-deposition electrical poling was required to align the dipoles. Single layer samples could be post poled, though the area of poling was quite small.…”
Section: Discussionmentioning
confidence: 99%
“…By applying a voltage to the hot end of a 3D printer, Lee"s group was able to acquire individual piezoelectric PVDF extradite fibers that generated charge when flexed. In addition, Bian, et al, created a PVDF covered metal molybdenum fiber, electrically poled the structure, and then used the fiber as an air flow sensor [13]. Voltage responses for Bian"s 10 mm long 0.4 mm diameter fibers were in the 100"s of µV range for air flow rates of 0 to 18 m s -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Using a similar method, Bian et al . demonstrated a metal-core piezoelectric fiber that had a PVDF sheath and a molybdenum filament core 21 . Recently, Martins et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lund et al reported the melt-spinning of a PVDF-yarn with a conductive carbon black/polypropylene (CB/PP) core 20 . Using a similar method, Bian et al demonstrated a metal-core piezoelectric fiber that had a PVDF sheath and a molybdenum filament core 21 .…”
mentioning
confidence: 99%
“…More importantly, the piezoelectric fiber retained its performance even after three days' cyclic bend-release tests. Compared to other piezoelectric fibers [20][21][22][23]28 , the fibers presented in this work feature a swiss roll structure of the piezoelectric layer, which considerably increases the active surface area and reduces the layer thickness, this resulting in considerably higher voltages and currents (and consequently electric powers) that can be generated by such fibers. Large-area piezoelectric textiles could be fabricated by incorporating the drawn fibers into woven fabrics, thanks to their excellent mechanical properties (as they are made only of plastics), and the use of low-cost, high volume fabrication techniques (fiber drawing).…”
mentioning
confidence: 99%